Coating Characterization in CrN Deposited by Magnetron Sputtering Method on AISI 316 Steel - I. Hilerio (The Minerals, Metals and Materials Society, 2009)
Chromium Nitride (CrN) thin films were deposited on AISI steel 316 substrates by means of the reactive magnetron sputtering method. CrN films were produced under two different conditions. In the first one, the substrate was heated by a DC source. For the second coating a negative substrate bias voltage was applied. X ray diffraction, quantitative energy dispersion and scanning electron microscope were employed to characterize the two different phases, their chemical composition as well as their microstructure. In addition, a microhardness test was carried out. The results show that a better phase formation of CrN thin films was achieved when a heating source was present (first case). Both coatings presented homogeneous surface. Their compositions show differences even when the gases flowing are the same in composition. Regarding to the hardness test results, there can be found a higher value when using a heating source.